RESEARCH TITLE: MODEL TO DEVELOP THE DESIRABLE CHARACTERISTICS FOR ADMINISTRATORS IN INSTITUTE OF PHYSICAL EDUCATION - ม่วงมี สุชิน (RMUTT Global Business and Economics Review, 2015)
The purposes of this research were: 1) to study desirable characteristics for Administrators in Institute of Physical Education. 2) to Design desirable characteristics model. 3) to study the possibility of using desirable characteristics model. The methodology of the study comprised of the following steps: 1) analyzing the documents concerning the characteristic for administrators; 2) designing and testing the questionnaires about the administrators’ desirable characteristics. 3) developing and creating characteristics for administrators. 4) developing the desirable characteristics by using Delphi technique and confirmatory factor analysis. 5) finding the suggested information to create the desirable characteristics. The statistical pieces of device use for this study were percentage, median and interquartile range. The results of this research revealed six aspects of the desirable characteristics for administrators in Institute of Physical Education, which were as follows : 1) skills and knowledge of administrative work and expertise in the area of physical education; 2) unifying and coordination skills; 3) flexible to change, understanding of the nature of paradigm change and change leader; 4) being honest and ethical; 5) involved and being a hard-working; 6) respectable person, having the right personality and being a good role model. The results of Delphi technique and confirmatory factor analysis were confirmed. According to the information displayed, the results revealed that the administrators’ training curriculum and the assessment of the training manuals all criteria were acceptable. The experts had approved all criteria to be used.